DRAMA SEBAGAI MEDIA PENGAJARAN BAHASA INGGRIS BAGI YL (YOUNG LEARNERS) - Widayanti, Maria Johana Ari (Lembaran Ilmu Kependidikan, 2010)
Drama for teaching English for elementary school students is a real communicationinvolving ideas, emotions, feelings, and adaptations. Drama in young learners (YL)classrooms allows shy students to Ã¢â¬Åhide behindÃ¢â¬Â the character when they speakEnglish. There are some reasons underlying the use of drama for teaching English toyoung learners: (a) Drama helps children to activate language and have fun. Itencourages children to speak and allows to communicate, even with limited language,using nonverbal communication, such as body movements and facial expressions; (b)Drama is familiar to children. Dramatizing has been a part of childrens lives sincetheir early age. They pretend to be adults in situations that are close to the reality. Theyalso behave as adults when they play their roles; (c) Drama helps children build theirconfidence. It means that by taking on a role, children can escape from everydayidentity. This is useful for children who are reluctant to use English or who do not likeworking in groups; (d) Drama dynamically nurtures childrens cooperative ability in agroup.Kata Kunci : drama, media pengajaran, young learners